TIME DEPENDENT ANTIOXIDANT ACTIVITY OF FRESH JUICE OF LEAVES OF CORIANDRUM SATIVUM (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
The antioxidant activities of fresh juice of Coriandrum sativum was evaluated by various methods in vivo. Scavenging effects on the hydroxyl and super oxide radicals, level of glutathione and protection against reactive oxygen species induced lipid were evaluated. The fresh juice exhibited high antioxidant activities, evidenced by its ability to scavenge hydroxyl- and superoxide-radicals, high reducing power, and protection against biological macromolecular oxidative damage and by increasing the level of glutathione. Presence of flavonoids confirms its antioxidant activity. In conclusion, these results demonstrate potential antioxidant activity of fresh juice of Coriandrum sativum.